China's Assertiveness and the Indo-Pacific Response: Australia's Strategic Calculus - Ping, Jonathan; Chan, Edward Sing Yue (INTERNATIONAL JOURNAL OF CHINA STUDIES, 2025)
After decades of economic success and relative political stability at home, the Communist Party of China (CPC) has become confident in its government model, particularly in the wake of its successful navigation of the 2008 Global Financial Crisis. The Party's growing confidence in China's rise and its grip on power has fuelled a more assertive foreign policy on the global stage. This article contends that China's global assertiveness - as experienced and responded by Australia - if taken too far, could ultimately weaken the Party at home. This is because the Party's economic sucesses have been a result of the PRC's successful integration into the world economy and maintenance of harmonious trade relations with the world's major economies.